2018
DOI: 10.1186/s40345-017-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-based objective monitoring in bipolar disorder: status and considerations

Abstract: In 2001, the WHO stated that: “The use of mobile and wireless technologies to support the achievement of health objectives (mHealth) has the potential to transform the face of health service delivery across the globe”. Within mental health, interventions and monitoring systems for depression, anxiety, substance abuse, eating disorder, schizophrenia and bipolar disorder have been developed and used. The present paper presents the status and findings from studies using automatically generated objective smartphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 70 publications
0
59
0
Order By: Relevance
“…The analysis showed that CBT programs with sessions of 90 min or more are most effective, and the efficacy is more enhanced for bipolar I disorder than bipolar II disorder. In the era of information technology, the efficacy of computerized CBT or smartphone‐based activity monitoring on treatment of BD is an issue that urgently requires study. Negative cognitive style, which is the target of CBT and causes vulnerability to depression, is reportedly associated with hyperactivation of the amygdala .…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…The analysis showed that CBT programs with sessions of 90 min or more are most effective, and the efficacy is more enhanced for bipolar I disorder than bipolar II disorder. In the era of information technology, the efficacy of computerized CBT or smartphone‐based activity monitoring on treatment of BD is an issue that urgently requires study. Negative cognitive style, which is the target of CBT and causes vulnerability to depression, is reportedly associated with hyperactivation of the amygdala .…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Moreover, as it has already been demonstrated, passive behaviour information (i.e. without users input) captured from the smartphone usage and sensors could enhance the precision of clinical algorithms and could represent a paradigm shift in mood tracking methods (Faurholt-Jepsen et al, 2018, 2015Hidalgo-Mazzei et al, 2018). The next version of SIMPLe (i.e.…”
Section: Accepted Manuscript Limitationsmentioning
confidence: 99%
“…Smartphone-based monitoring is a potential solution [2]. Smartphones can passively collect behavioral data relevant to mood, and smartphone ownership is becoming increasingly ubiquitous [3], meaning such an approach could help to make mental health care more widely accessible.…”
Section: Introductionmentioning
confidence: 99%